The education of the Indian in Natal,(1860-1947). Volume Two. - Cooppan,Somarsundarum (Department of Philosophy, 2023)
The educational development 0f a people 1s influenced by various factors - political, economic and social. The growth of Indian education in Natal must be studied in this context. In May, 1910, the tour self-governing colonies of Natal, the Traneval orange Free State and. the Cape amalgamated. under one central government to form the Union of South Africa. This event marks the birth of a new era in South African history.